Functional TRPV6 channels are crucial for transepithelial Ca2+ absorption - Woudenberg-Vrenken, Titia E.; Freichel, Marc (American journal of physiology. Gastrointestinal and liver physiology, 2012)
TRPV6 is considered the primary protein responsible for transcellular Ca2+ absorption. In vitro studies demonstrate that a negatively charged amino acid (D) within the putative pore region of mouse TRPV6 (position 541) is critical for Ca2+ permeation of the channel. To elucidate the role of TRPV6 in transepithelial Ca2+ transport in vivo, we functionally analyzed a TRPV6D541A/D541A knockin mouse model. After weaning, mice were fed a regular (1% wt/wt) or Ca2+-deficient (0.02% wt/wt) diet and housed in metabolic cages. Blood was sampled for Ca2+ measurements, and the expression of Ca2+ transport proteins was analyzed in kidney and duodenum. Intestinal 45Ca2+ uptake was measured in vivo by an absorption assay. Challenging the mice with the Ca2+-deficient diet resulted in hypocalcemia in wild-type and TRPV6D541A/D541A mice. On a low-Ca2+ diet both mouse strains displayed increased expression of intestinal TRPV6, calbindin-D9K, and renal TRPV5. TRPV6D541A/D541A mice showed significantly impaired intestinal Ca2+ uptake compared with wild-type mice, and duodenal TRPV5 expression was increased in TRPV6D541A/D541A mice. On a normal diet, serum Ca2+ concentrations normalized in both mouse strains. Under these conditions, intestinal Ca2+ uptake was similar, and the expression levels of renal and intestinal Ca2+ transport proteins were not affected. We demonstrate that TRPV6D541A/D541A mice exhibit impaired transcellular Ca2+ absorption. Duodenal TRPV5 expression was increased in TRPV6D541A/D541A mice, albeit insufficient to correct for the diminished Ca2+ absorption. Under normal conditions, when passive Ca2+ transport is predominant, no differences between wild-type and TRPV6D541A/D541A mice were observed. Our results demonstrate a specific role for TRPV6 in transepithelial Ca2+ absorption.
Gesehen am 15.10.2018